1992
DOI: 10.1021/ja00033a031
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and mechanistic studies on the antitumor antibiotics esperamicin A1 and calicheamicin .gamma.1: synthesis of 2-ketobicyclo[7.3.1.]enediyne and 13-ketocyclo[7.3.1]enediyne cores mediated by .eta.2]dicobalt hexacarbonyl alkyne complexes. Cycloaromatization rate studies

Abstract: M«0'^S^V'NH 'o chemists can play a leading role here. From their experiences in probing reaction mechanisms in vitro they can postulate likely intermediate metabolites and design experiments to follow the reaction sequences of drugs".2The majority of antitumor antibiotics inhibit cell division by interfering with the synthesis or use of nucleic acids.3 There is a constant need to discover new agents that interact with DNA in a mechanistically definable manner.4 In 1987 the Lederle5 and Bristol-Myers6 groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(36 citation statements)
references
References 1 publication
1
35
0
Order By: Relevance
“…Magnus et al . found that the strain increased by 1.5 kcal·mol −1 (MM2/PRDDO) in moving from R to TS for 13 , but that strain was relieved by 6.0 kcal·mol −1 for the six-membered ring compound 12 74,120. This release is attributed to a boat-chair strain release mechanism available to the 6-membered ring, but not the 5-membered ring.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Magnus et al . found that the strain increased by 1.5 kcal·mol −1 (MM2/PRDDO) in moving from R to TS for 13 , but that strain was relieved by 6.0 kcal·mol −1 for the six-membered ring compound 12 74,120. This release is attributed to a boat-chair strain release mechanism available to the 6-membered ring, but not the 5-membered ring.…”
Section: Discussionmentioning
confidence: 96%
“…Calculation of strain relief using molecular mechanics allowed Magnus et al . to rationalize the rates of reaction as stemming more from strain relief than the separation of the acetylenic carbons 74,120. For the 6-membered ring in 12 , a boat to chair conversion in moving to products released more strain than was alleviated in the 5-membered case.…”
Section: Discussionmentioning
confidence: 99%
“…These considerations are especially important for bicyclic enediynes, or those possessing bulky substituents at the alkyne termini positions. To this end, Magnus used MM2 force-field calculations to explain the reactivities of a series of bicyclic enediynes, 66 and Maier subsequently developed an improved model to calculate the difference in strain energies between reactants and products in order to accurately predict enediyne …”
Section: Geometric Factors Influencing Bergman Cyclizationmentioning
confidence: 99%
“…The first step is the copper-catalyzed addition of a,o-diynes to manganese carbyne complexes to give an intermediate bis(alkynylcarbene) species that rearranges to an enediyne unit below room temperature. In the second step, the manganese catalyst, which Magnus has been used effectively as an alkyne protecting-stabilizing group in natural product syntheses (378)(379)(380)(381)(382)(383), is released from the enediyne by photolysis, copper-catalyzed air oxidation, or stoichiometric Cu(II) oxidation. These new procedures have been applied to a variety of five-, six-, and seven-membered ring cyclic enediynes containing a range of ether, ester, and ketone functional groups (Scheme 31).…”
Section: Ligand Transformations and Reactivitymentioning
confidence: 99%